The Performance of Universal Banks: Evidence from Switzerland - Bertrand Rime; Kevin J. Stiroh (Swiss National Bank, Study Center Gerzensee, 2001)
This paper examines the production structure of Swiss banks in the period 1996-99. Using a variety of output specifications, we find evidence of large relative inefficiencies across Swiss banks. The results show the importance of accounting for the broad range of activities that universal banks undertake, e.g., failure to account for off-balance sheet items, trading, and brokerage and portfolio management activities leads profit efficiency to be dramatically understated. We find evidence of economies of scale for small and mid-size banks, but little evidence that significant scale economies remain for the very largest banks. Finally, evidence on scope economies is weak for the largest banks that are involved in a wide variety of activities. These results suggest few obvious benefits from the trend toward larger universal banks.
Keywords: 330; Bank; Skalenertrag; Unternehmenserfolg; Schweiz